Analisis Dampak Alih Fungsi Lahan Pertanian Ke Industri Terhadap Hasil Produksi Tanaman Pangan Di Cilegon - Alben Abimayu; Erlin Kurniati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research aims to analyze the impact of conversion of agricultural land to industry on food crop production in Cilegon. The research method used is qualitative by conducting case studies and field data analysis. The results of this research provide an in-depth understanding of the consequences of land conversion on food crop production in the area. It is hoped that these findings can provide input for sustainable management of agricultural and industrial land. So that farmers experience sustainable prosperity.